Novel treatment options for nonmelanoma skin cancer: focus on electronic brachytherapy - Kasper ME (Dove Medical Press, 2015)
Michael E Kasper,1,2 Ahmed A Chaudhary3 1Department of Radiation Oncology, Lynn Cancer Institute at Boca Raton Regional Hospital, Boca Raton, 2Charles E. Schmidt College of Medicine, Florida Atlantic University, FL, 3North Main Radiation Oncology, Warren Alpert School of Medicine, Brown University, RI, USA Abstract: Nonmelanoma skin cancer (NMSC) is an increasing health care issue in the United States, significantly affecting quality of life and impacting health care costs. Radiotherapy has a long history in the treatment of NMSC. Shortly after the discovery of X-rays and 226Radium, physicians cured patients with NMSC using these new treatments. Both X-ray therapy and brachytherapy have evolved over the years, ultimately delivering higher cure rates and lower toxicity. Electronic brachytherapy for NMSC is based on the technical and clinical data obtained from radionuclide skin surface brachytherapy and the small skin surface applicators developed over the past 25 years. The purpose of this review is to introduce electronic brachytherapy in the context of the history, data, and utilization of traditional radiotherapy and brachytherapy. Keywords: electronic brachytherapy, superficial radiotherapy, skin surface brachytherapy, electron beam therapy, nonmelanoma skin cancer, basal cell carcinoma, squamous cell carcinoma